E-Commerce Shop Helviah Skincare Mobile Application - Marlia Sari; Lusia Septia ER; Muhammad Junaidi (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
The rapid advancement of mobile technology has significantly transformed consumer behavior, accelerating the shift towards e-commerce as a dominant shopping method. Recognizing this trend, the Helviah Skincare Shop, a retailer specializing in skincare products, developed a mobile e-commerce application to enhance customer experience, streamline transactions, and expand its market reach. This research adopts a structured methodology encompassing problem identification, data collection, system design, development, and rigorous testing to create a user-friendly mobile platform tailored to the unique needs of skincare shoppers. The application features an intuitive product catalog, a secure payment gateway, personalized recommendations, and real-time order tracking, ensuring a seamless shopping experience. The results demonstrate a positive impact, with user feedback highlighting increased engagement, customer satisfaction, and accessibility to products. By effectively addressing consumer needs, the Helviah Skincare e-commerce application fosters customer loyalty, drives business growth, and positions the retailer as a competitive player in the e-commerce sector. This study contributes to the field of mobile commerce by showcasing a scalable solution that integrates technology and user-centered design to deliver tangible business outcomes.